The role of bank lending in ensuring economic growth - Чупринюк, Дмитро Олегович (Ірпінь, 2025)
Особистий внесок у межах дослідження полягає у пропозиціях щодо перспектив розвитку банківського кредитування як ключового інструменту забезпечення економічного зростання України. Зокрема, у розробленні напрямів удосконалення кредитної політики, що враховують специфіку воєнного часу.

My personal contribution within the research consists of proposals regarding the prospects for the development of bank lending as a key instrument for ensuring economic growth in Ukraine. In particular, in developing directions for improving credit policy that take into account the specifics of wartime.
Keywords: банківське кредитування; Україна; економічне зростання; цифрові технології; нормативно-правове регулювання; bank lending; Ukraine; economic growth; digital technologies; legal and regulatory framework